Konsep Doa Yesus Menurut Kallistos Ware: Sebuah Doa Membangun Spiritual Yang Kokoh - waruwu, damica23; Wijaya, Hendi (Sekolah Tinggi Teologi Kadesi Bogor, 2024)
Prayer is an important aspect for humans to ask for help from God, especially for Christians. However, humans mostly ask for God's help in times of need or in times of urgency and then they cry out for God's help through prayer or by mentioning the name of Jesus. Thus, in such a way, it will be more difficult for humans to get close to God. The purpose of this study is to explain how the Jesus Prayer can be the most important part of a Christian's life based on “The Power of the Name the Jesus Prayer in Orthodox spirituality”. The method used by the author in this research is a literature study, by reading books, magazines, and collecting library data. The author also interacts with other texts such as journals, and the writings of the church fathers. Therefore, the results of this study show that the prayer of the Jesus puja or praying by mentioning the name of Jesus can be done at any time, be it in distress or in happiness, because this prayer can help humans to be able to continue to establish a good and strong relationship with God without any restrictions, and can also bring humans to experience the likeness of God or called (theosis).